Association Between Caffeine Intake and Bowel Habits and Inflammatory Bowel Disease: A Population-Based Study - Yang X; Yan H; Chen Y; Guo R (Journal of Multidisciplinary Healthcare, 2025)
Xiaoxian Yang,1,2 Haiyi Yan,1 Yan Chen,1 Rui Guo1 1Department of Hepatology, Xiyuan Hospital of China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 2First Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of ChinaCorrespondence: Rui Guo, Xiyuan Hospital of China Academy of Chinese Medical Sciences, No. 1 Xiyuan Playground, Haidian District, Beijing, People’s Republic of China, Email GR1540128260@163.comBackground: The effect of caffeine in coffee, a popular beverage, on gastrointestinal symptoms has been the subject of ongoing debate worldwide. The present study explored the association between caffeine intake and bowel habits and Inflammatory bowel disease (IBD).Methods: Data from the National Health and Nutrition Examination Survey (NHANES) spanning 2005– 2010 were utilized for this cross-sectional survey. Bowel habits and IBD were defined by self-report. Logistic regression models assessed the linear relationship between caffeine intake and chronic constipation. Nonlinear associations were delineated using fitted smoothed curves and threshold effect analyses. Finally, subgroup analyses and interactions were used to test the stability of the findings.Results: This population-based study included a total of 12,759 adults. We found that caffeine intake was negatively associated with chronic diarrhea. There was a U-shaped nonlinear relationship between caffeine intake and chronic constipation. To the left of breakpoint 2.04 (100 mg/1 unit), caffeine intake was negatively associated with chronic constipation (OR [95% CI]: 0.82 [0.74, 0.90]), however, to the right of the breakpoint, there was a positive association (OR [95% CI]: 1.06 [1.00, 1.12]). In addition, no significant association was found between caffeine intake and IBD. Subgroup analyses and interaction tests showed that caffeine intake was simply negatively associated with chronic constipation in older adults.Conclusion: In conclusion, moderate caffeine intake may help with bowel movements, but excessive caffeine intake may cause chronic constipation. Appropriate caffeine intake in older adults may help prevent chronic constipation. This suggests that in our clinical practice, we need to strategize caffeine intake according to the population’s defecation status.Keywords: caffeine intake, chronic constipation, chronic diarrhea, U-shaped, NHANES